Gulf War and Health: Volume 6: Physiologic, Psychologic, and Psychosocial Effects of Deployment-Related Stress - Institute of Medicine (The National Academies Press, 2008)
The sixth in a series of congressionally mandated reports on Gulf War veterans' health, this volume evaluates the health effects associated with stress. Since the launch of Operation Desert Storm in 1991, there has been growing concern about the physical and psychological health of Gulf War and other veterans. In the late 1990s, Congress responded by asking the National Academy of Sciences (NAS) to review and evaluate the scientific and medical literature regarding associations between illness and exposure to toxic agents, environmental or wartime hazards, and preventive medicines or vaccines in members of the armed forces who were exposed to such agents. Deployment to a war zone has a profound impact on the lives of troops and on their family members. There are a plethora of stressors associated with deployment, including constant vigilance against unexpected attack, difficulty distinguishing enemy combatants from civilians, concerns about survival, caring for the badly injured, and witnessing the death of a person. Less traumatic but more pervasive stressors include anxiety about home life, such as loss of a job and income, impacts on relationships, and absence from family. The focus of this report, by the Institute of Medicine (IOM) Committee on Gulf War and Health: Physiologic, and Psychosocial Effects of Deployment-Related Stress, is the long-term effects of deployment-related stress. Gulf War and Health: Volume 6. Physiologic, and Psychosocial Effects of Development Related Stress evaluates the scientific literature regarding association between deployment-related stressors and health effects, and provides meaningful recommendations to remedy this problem.

Monitoring Metabolic Status: Predicting Decrements in Physiological and Cognitive Performance - Institute of Medicine (The National Academies Press, 2004)
The U.S. military2019s concerns about the individual combat service member2019s ability to avoid performance degradation, in conjunction with the need to maintain both mental and physical capabilities in highly stressful situations, have led to and interest in developing methods by which commanders can monitor the status of the combat service members in the field. This report examines appropriate biological markers, monitoring technologies currently available and in need of development, and appropriate algorithms to interpret the data obtained in order to provide information for command decisions relative to the physiological 201creadiness201d of each combat service member. More specifically, this report also provides responses to questions posed by the military relative to monitoring the metabolic regulation during prolonged, exhaustive efforts, where nutrition\/hydration and repair mechanisms may be mismatched to intakes and rest, or where specific metabolic derangements are present.

Nonhuman Primate Models in Biomedical Research: State of the Science and Future Needs - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Nonhuman primates represent a small fraction of animals used in biomedical research, but they remain important research models due to their similarities to humans with respect to genetic makeup, anatomy, physiology, and behavior. Limitations in the availability of nonhuman primates have been exacerbated by the COVID-19 pandemic and recent restrictions on their exportation and transportation, impacting National Institutes of Health (NIH)-funded research necessary for both public health and national security. Additionally, there is continued interest in understanding whether and how nonanimal models can be used to answer scientific questions for which nonhuman primates are currently used. At the direction of the U.S. Congress, NIH asked the National Academies of Sciences, Engineering, and Medicine to convene an expert committee to conduct a landscape analysis of current and future use of nonhuman primates in NIH-supported biomedical research, as well as opportunities for new approach methodologies to complement or reduce reliance on nonhuman primate models. This report provides the committee findings and conclusions.

Evaluating the HRSA Traumatic Brain Injury Program - Institute of Medicine (The National Academies Press, 2006)
A traumatic brain injury (TBI)2014a brain injury caused by a sudden jolt, blow, or penetrating head trauma that disrupts the function of the brain2014can happen to anyone. The effects of a TBI vary from person to person, depending on the force dynamics of injury and the patient's anatomy and physiology. People with TBI-related disabilities and their family members and caregivers need comprehensive, coordinated, person-centered systems of care that attend to their changing needs long after their acute injury has been treated medically. At least 5.3 million Americans are estimated to have a TBI-related disability. The Health Resources and Services Administration's (HRSA) TBI Program, initially authorized by the Traumatic Brain Injury Act of 1996 (P.L. 104-106) and reauthorized by the Children's Health Act of 2000 is a modest federal program with broad ambitions: a 9 million grants program aimed at motivating states to create systems improvement on behalf of persons with TBI with disabilities and their families. In 2004, the federal Office of Management and Budget (OMB) questioned the effectiveness of the HRSA TBI Program, noting that there had been no regular independent evaluations of the program's effects on TBI patients and their families. To address these concerns, HRSA contracted with the Institute of Medicine (IOM) in the spring of 2005 to conduct a study: (1) to assess the impact of the HRSA Program on how state systems are working or failing to work in support of individuals with TBI; and (2) to advise HRSA on how it could improve the program to best serve individuals with TBI and their families. The IOM appointed an 11-member Committee on Traumatic Brain Injury to perform the study. This report presents the IOM Committee on Traumatic Brain Injury's assessment of the HRSA TBI Program's impact and recommendations for improving the program.

Temporomandibular Disorders: Priorities for Research and Care - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Temporomandibular disorders (TMDs), are a set of more than 30 health disorders associated with both the temporomandibular joints and the muscles and tissues of the jaw. TMDs have a range of causes and often co-occur with a number of overlapping medical conditions, including headaches, fibromyalgia, back pain and irritable bowel syndrome. TMDs can be transient or long-lasting and may be associated with problems that range from an occasional click of the jaw to severe chronic pain involving the entire orofacial region. Everyday activities, including eating and talking, are often difficult for people with TMDs, and many of them suffer with severe chronic pain due to this condition. Common social activities that most people take for granted, such as smiling, laughing, and kissing, can become unbearable. This dysfunction and pain, and its associated suffering, take a terrible toll on affected individuals, their families, and their friends. Individuals with TMDs often feel stigmatized and invalidated in their experiences by their family, friends, and, often, the health care community. Misjudgments and a failure to understand the nature and depths of TMDs can have severe consequences - more pain and more suffering - for individuals, their families and our society. Temporomandibular Disorders: Priorities for Research and Care calls on a number of stakeholders - across medicine, dentistry, and other fields - to improve the health and well-being of individuals with a TMD. This report addresses the current state of knowledge regarding TMD research, education and training, safety and efficacy of clinical treatments of TMDs, and burden and costs associated with TMDs. The recommendations of Temporomandibular Disorders focus on the actions that many organizations and agencies should take to improve TMD research and care and improve the overall health and well-being of individuals with a TMD.

Traumatic Brain Injury: A Roadmap for Accelerating Progress - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Every community is affected by traumatic brain injury (TBI). Causes as diverse as falls, sports injuries, vehicle collisions, domestic violence, and military incidents can result in injuries across a spectrum of severity and age groups. Just as the many causes of TBI and the people who experience it are diverse, so too are the physiological, cognitive, and behavioral changes that can occur following injury. The overall TBI ecosystem is not limited to healthcare and research, but includes the related systems that administer and finance healthcare, accredit care facilities, and provide regulatory approval and oversight of products and therapies. TBI also intersects with the wide range of community organizations and institutions in which people return to learning, work, and play, including the education system, work environments, professional and amateur sports associations, the criminal justice system, and others. Traumatic Brain Injury: A Roadmap for Accelerating Progress examines the current landscape of basic, translational, and clinical TBI research and identifies gaps and opportunities to accelerate research progress and improve care with a focus on the biological, psychological, sociological, and ecological impacts. This report calls not merely for improvement, but for a transformation of attitudes, understanding, investments, and care systems for TBI.

Delivering High-Quality Cancer Care: Charting a New Course for a System in Crisis - Institute of Medicine (The National Academies Press, 2013)
In the United States, approximately 14 million people have had cancer and more than 1.6 million new cases are diagnosed each year. However, more than a decade after the Institute of Medicine (IOM) first studied the quality of cancer care, the barriers to achieving excellent care for all cancer patients remain daunting. Care often is not patient-centered, many patients do not receive palliative care to manage their symptoms and side effects from treatment, and decisions about care often are not based on the latest scientific evidence. The cost of cancer care also is rising faster than many sectors of medicine2014having increased to 125 billion in 2010 from 72 billion in 20042014and is projected to reach 173 billion by 2020. Rising costs are making cancer care less affordable for patients and their families and are creating disparities in patients' access to high-quality cancer care. There also are growing shortages of health professionals skilled in providing cancer care, and the number of adults age 65 and older2014the group most susceptible to cancer2014is expected to double by 2030, contributing to a 45 percent increase in the number of people developing cancer. The current care delivery system is poorly prepared to address the care needs of this population, which are complex due to altered physiology, functional and cognitive impairment, multiple coexisting diseases, increased side effects from treatment, and greater need for social support. Delivering High-Quality Cancer Care: Charting a New Course for a System in Crisis presents a conceptual framework for improving the quality of cancer care. This study proposes improvements to six interconnected components of care: (1) engaged patients; (2) an adequately staffed, trained, and coordinated workforce; (3) evidence-based care; (4) learning health care information technology (IT); (5) translation of evidence into clinical practice, quality measurement and performance improvement; and (6) accessible and affordable care. This report recommends changes across the board in these areas to improve the quality of care. Delivering High-Quality Cancer Care: Charting a New Course for a System in Crisis provides information for cancer care teams, patients and their families, researchers, quality metrics developers, and payers, as well as HHS, other federal agencies, and industry to reevaluate their current roles and responsibilities in cancer care and work together to develop a higher quality care delivery system. By working toward this shared goal, the cancer care community can improve the quality of life and outcomes for people facing a cancer diagnosis.

Exploring the Biological Contributions to Human Health: Does Sex Matter? - Institute of Medicine (The National Academies Press, 2001)
It's obvious why only men develop prostate cancer and why only women get ovarian cancer. But it is not obvious why women are more likely to recover language ability after a stroke than men or why women are more apt to develop autoimmune diseases such as lupus. Sex differences in health throughout the lifespan have been documented. Exploring the Biological Contributions to Human Health begins to snap the pieces of the puzzle into place so that this knowledge can be used to improve health for both sexes. From behavior and cognition to metabolism and response to chemicals and infectious organisms, this book explores the health impact of sex (being male or female, according to reproductive organs and chromosomes) and gender (one's sense of self as male or female in society). Exploring the Biological Contributions to Human Health discusses basic biochemical differences in the cells of males and females and health variability between the sexes from conception throughout life. The book identifies key research needs and opportunities and addresses barriers to research. Exploring the Biological Contributions to Human Health will be important to health policy makers, basic, applied, and clinical researchers, educators, providers, and journalists-while being very accessible to interested lay readers.

Gulf War and Health: Volume 1: Depleted Uranium, Sarin, Pyridostigmine Bromide, and Vaccines - Institute of Medicine (The National Academies Press, 2000)
The men and women who served in the Gulf War theater were potentially exposed to a wide range of biological and chemical agents. Gulf War and Health: Volume 1 assesses the scientific literature concerning the association between these agents and the adverse health effects currently experienced by a large number of veterans.

Multiple Sclerosis: Current Status and Strategies for the Future - Institute of Medicine (The National Academies Press, 2001)
Multiple sclerosis is a chronic and often disabling disease of the nervous system, affecting about 1 million people worldwide. Even though it has been known for over a hundred years, no cause or cure has yet been discovered2014but now there is hope. New therapies have been shown to slow the disease progress in some patients, and the pace of discoveries about the cellular machinery of the brain and spinal cord has accelerated. This book presents a comprehensive overview of multiple sclerosis today, as researchers seek to understand its processes, develop therapies that will slow or halt the disease and perhaps repair damage, offer relief for specific symptoms, and improve the abilities of MS patients to function in their daily lives. The panel reviews existing knowledge and identifies key research questions, focusing on: Research strategies that have the greatest potential to understand the biological mechanisms of recovery and to translate findings into specific strategies for therapy. How people adapt to MS and the research needed to improve the lives of people with MS. Management of disease symptoms (cognitive impairment, depression, spasticity, vision problems, and others). The committee also discusses ways to build and financially support the MS research enterprise, including a look at challenges inherent in designing clinical trials. This book will be important to MS researchers, research funders, health care advocates for MS research and treatment, and interested patients and their families.

Non-Heart-Beating Organ Transplantation: Practice and Protocols - Institute of Medicine (The National Academies Press, 2000)
In 1997, the Institute of Medicine published a report entitled Non-Heart- Beating Organ Transplantation: Medical and Ethical Issues in Procurement. The findings and recommendations of that study defined the ethical and scientific basis for non-heart-beating organ donation and transplantation, and provided specific recommendations for practices that affirm patient welfare, promote patient and family choice, and avoid conflicts of interest. Following the 1997 study, the Department of Health and Human Services requested a follow up study to promote such efforts. The central activity for this study was a workshop held in Washington, D.C., on May 24-25, 1999. The workshop provided the opportunity for extensive dialogue on non-heart-beating organ donation among hospitals and organ procurement organizations (OPOs) that are actively involved in non-heartbeating organ and tissue donation and those with concerns about whether and how to proceed. The findings and recommendations of this report are based in large measure on the discussions and insights from that workshop. Non-Heart-Beating Organ Transplantation includes seven recommendations for developing and implementing non-heart-beating-donor protocols. These recommendations were based on the findings and recommendations from the 1997 IOM report and consensus achieved among participants at the national workshop. The committee developed these recommendations as steps towards an approach to non-heart-beating-donor organ donation and procurement consistent with underlying scientific and ethical guidelines, patient and family options and choices, and public trust in organ donation.

Addressing Sickle Cell Disease: A Strategic Plan and Blueprint for Action - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Sickle cell disease (SCD) is a genetic condition that affects approximately 100,000 people in the United States and millions more globally. Individuals with SCD endure the psychological and physiological toll of repetitive pain as well as side effects from the pain treatments they undergo. Some adults with SCD report reluctance to use health care services, unless as a last resort, due to the racism and discrimination they face in the health care system. Additionally, many aspects of SCD are inadequately studied, understood, and addressed. Addressing Sickle Cell Disease examines the epidemiology, health outcomes, genetic implications, and societal factors associated with SCD and sickle cell trait (SCT). This report explores the current guidelines and best practices for the care of patients with SCD and recommends priorities for programs, policies, and research. It also discusses limitations and opportunities for developing national SCD patient registries and surveillance systems, barriers in the healthcare sector associated with SCD and SCT, and the role of patient advocacy and community engagement groups.

Beyond Myalgic Encephalomyelitis/Chronic Fatigue Syndrome: Redefining an Illness - Institute of Medicine (The National Academies Press, 2015)
Myalgic encephalomyelitis (ME) and chronic fatigue syndrome (CFS) are serious, debilitating conditions that affect millions of people in the United States and around the world. ME\/CFS can cause significant impairment and disability. Despite substantial efforts by researchers to better understand ME\/CFS, there is no known cause or effective treatment. Diagnosing the disease remains a challenge, and patients often struggle with their illness for years before an identification is made. Some health care providers have been skeptical about the serious physiological - rather than psychological - nature of the illness. Once diagnosed, patients often complain of receiving hostility from their health care provider as well as being subjected to treatment strategies that exacerbate their symptoms. Beyond Myalgic Encephalomyelitis\/Chronic Fatigue Syndrome proposes new diagnostic clinical criteria for ME\/CFS and a new term for the illness - systemic exertion intolerance disease(SEID). According to this report, the term myalgic encephalomyelitis does not accurately describe this illness, and the term chronic fatigue syndrome can result in trivialization and stigmatization for patients afflicted with this illness. Beyond Myalgic Encephalomyelitis\/Chronic Fatigue Syndrome stresses that SEID is a medical - not a psychiatric or psychological - illness. This report lists the major symptoms of SEID and recommends a diagnostic process.One of the report's most important conclusions is that a thorough history, physical examination, and targeted work-up are necessary and often sufficient for diagnosis. The new criteria will allow a large percentage of undiagnosed patients to receive an accurate diagnosis and appropriate care. Beyond Myalgic Encephalomyelitis\/Chronic Fatigue Syndrome will be a valuable resource to promote the prompt diagnosis of patients with this complex, multisystem, and often devastating disorder; enhance public understanding; and provide a firm foundation for future improvements in diagnosis and treatment.

Biologic Markers in Pulmonary Toxicology - National Research Council (The National Academies Press, 1989)
Biologic markers2014indicators of biological exposure or change2014offer the promise of early detection of disease caused by environmental exposure. Researchers have used these markers to discover indications of pulmonary damage from low-level ozone, a finding with serious implications for health professionals and environmental regulators. Biologic Markers in Pulmonary Toxicology is a comprehensive study of this use of biologic markers. Focusing on the respiratory tract as an entryway for airborne pollutants, this volume reviews new ways of measuring markers, the need for markers to indicate dose or exposure levels, noninvasive respiratory function tests for use with healthy humans to detect sensitivity to inhaled pollutants, approaches to evaluating markers down to the cellular and biochemical levels, and more.

Reducing Suicide: A National Imperative - Institute of Medicine (The National Academies Press, 2002)
Every year, about 30,000 people die by suicide in the U.S., and some 650,000 receive emergency treatment after a suicide attempt. Often, those most at risk are the least able to access professional help. Reducing Suicide provides a blueprint for addressing this tragic and costly problem: how we can build an appropriate infrastructure, conduct needed research, and improve our ability to recognize suicide risk and effectively intervene. Rich in data, the book also strikes an intensely personal chord, featuring compelling quotes about people2019s experience with suicide. The book explores the factors that raise a person2019s risk of suicide: psychological and biological factors including substance abuse, the link between childhood trauma and later suicide, and the impact of family life, economic status, religion, and other social and cultural conditions. The authors review the effectiveness of existing interventions, including mental health practitioners2019 ability to assess suicide risk among patients. They present lessons learned from the Air Force suicide prevention program and other prevention initiatives. And they identify barriers to effective research and treatment. This new volume will be of special interest to policy makers, administrators, researchers, practitioners, and journalists working in the field of mental health.

Sleep Disorders and Sleep Deprivation: An Unmet Public Health Problem - Institute of Medicine (The National Academies Press, 2006)
Clinical practice related to sleep problems and sleep disorders has been expanding rapidly in the last few years, but scientific research is not keeping pace. Sleep apnea, insomnia, and restless legs syndrome are three examples of very common disorders for which we have little biological information. This new book cuts across a variety of medical disciplines such as neurology, pulmonology, pediatrics, internal medicine, psychiatry, psychology, otolaryngology, and nursing, as well as other medical practices with an interest in the management of sleep pathology. This area of research is not limited to very young and old patients2014sleep disorders reach across all ages and ethnicities. Sleep Disorders and Sleep Deprivation presents a structured analysis that explores the following: Improving awareness among the general public and health care professionals. Increasing investment in interdisciplinary somnology and sleep medicine research training and mentoring activities. Validating and developing new and existing technologies for diagnosis and treatment. This book will be of interest to those looking to learn more about the enormous public health burden of sleep disorders and sleep deprivation and the strikingly limited capacity of the health care enterprise to identify and treat the majority of individuals suffering from sleep problems.

Dispelling the Myths About Addiction: Strategies to Increase Understanding and Strengthen Research - Institute of Medicine (The National Academies Press, 1997)
Every year about half a million men, women, and children in the United States die from the effects of using nicotine, alcohol, and illegal drugs: one of every four American deaths. Yet research to solve this terrible problem is often perceived as less important than other types of biomedical investigation. Focusing on four major classes of drugs with the greatest social and economic impact2014nicotine, alcohol, opioids, and stimulants2014Dispelling the Myths About Addiction examines what is known about addiction and what is needed to develop a talented cadre of investigators and to educate the public about addiction research. The committee explores these areas: Economic costs of addiction. What has been learned about addiction from research into basic neurobiology and the brain, psychosocial and behavioral factors, and epidemiology. Education and training of researchers and the research infrastructure. Public perceptions and their impact on public policy in this field. This volume outlines the challenges and opportunities in addiction research today and makes recommendations to educators, treatment professionals, public and private institutions, and others for how to build support for addiction research and treatment.

Informing the Future: Critical Issues in Health: Second Edition - Institute of Medicine (The National Academies Press, 2003)

Oral Contraceptives and Breast Cancer - Institute of Medicine (The National Academies Press, 1991)
At least 10.7 million American women use oral contraceptives (OCs). The potential connection with breast cancer has caused concern among these OC users and uncertainty among many of their physicians. This new volume offers the most up-to-date information available on this critical topic. While the best available knowledge does not support any fundamental change in clinical practice with respect to the use of OCs, this book offers specific recommendations for more research to fully resolve the relationship between OCs and breast cancer. Noting consumer confusion, the volume includes a concise summary of benefits, risks, and other practical information for contraceptive users and their doctors. The volume presents current data on changes in patterns of OC use, differences in risk at different ages, the benefits of OCs, and more. Oral Contraceptives and Breast Cancer will be important reading for obstetricians\/gynecologists and other health professionals, their patients who use OCs, contraceptive manufacturers, women's health advocates, policymakers, and researchers.

Addressing the Nation's Changing Needs for Biomedical and Behavioral Scientists - National Research Council (The National Academies Press, 2000)
As biomedical and behavioral research progresses into new areas, the number of scientists active in various fields rises and falls, and the health needs of the U.S. population evolve, it is important to ensure that the preparation of future investigators reflects these changes. This book addresses these topics by considering questions such as the following: What is the current supply of biomedical and behavioral scientists? How is future demand for scientists likely to be affected by factors such as advances in research, trends in the employment of scientists, future research funding, and changes in health care delivery? What are the best ways to prepare prospective investigators to meet future needs in scientific research? In the course of addressing these questions, this volume examines the number of investigators trained every year, patterns of hiring by universities and industry, and the age of the scientific workforce in different fields, and makes recommendations for the number of scientists that should be trained in the years ahead. This book also considers the diversity of the research workforce and the importance of providing prospective scientists with the skills to successfully collaborate with investigators in related fields, and offers suggestions for how government and universities should structure their research training programs differently in the future.